Dominance has a biogeographical component: do plants tend to exert stronger impacts in their invaded rather than native range?. (20th June 2016) - Hejda, Martin; Štajerová, Kateřina; Pyšek, Petr
Abstract: Aim: Using three North American species invading Europe ( Aster novi‐belgii, Lupinus polyphyllus and Solidago canadensis ) and three European species invading North America ( Agrostis capillaris, Bromus tectorum and Cirsium arvense ), we tested (1) whether the dominant species impact differs between its native and invaded ranges and (2) whether the impacts differ according to the direction of invasion (from Europe to North America and vice versa). Location: North America (USA) and central Europe (Czech Republic). Methods: The dominance of the selected species was expressed as its relative cover, and its relationship to species richness was tested using marginal and mixed‐effect regression models. Results: All the three North American species invading Europe suppressed species richness in the native range, while only two ( A. novi‐belgii and L. polyphyllus ) impacted native species richness in the invaded range. On the contrary, of the three European species invading North America, only A. capillaris was found to suppress species richness in its native range, while all three suppressed it in the invaded range. Overall, the richness of native species responded significantly more negatively to the dominant species cover in its invaded rather than native range, regardless of the identity of the dominant species. Main conclusions: Invasive species suppress diversity more in the invaded range, and European invaders have more profound impacts in North America than North American invaders in Europe. We suggest that long‐term coexistence and species filtering are responsible for the lower impacts in the native range, while large‐scale evolutionary patterns are likely to be associated with the more profound impacts of selected European species as invaders in North America than vice versa.